(untitled) (Sindoro: Cendikia Pendidikan, 2025)
Cases of violence against special needs clients in a social institution show the weakness of the social protection system, especially in the supervision of social welfare institutions. Institutions that should provide protection actually become places where human rights violations occur. This study aims to analyze the role of social workers in handling these cases and identify strategies that can be applied to improve protection for special needs groups. Using a literature study approach and qualitative descriptive analysis, this study found that weak regulations, lack of effective complaint mechanisms, and low competence of social workers are the main factors that allow violence to occur in social institutions. Therefore, policy reforms in the form of improved regulations, training for social workers, and active community involvement are needed to create a safer and more inclusive social environment.